The bias in favor of pro-tariff lobbies - Fabella, Raul V. (Journal of Public Economics)
We show that the probability of success of the pro-tariff lobby, defined as a decreasing function of the ratio of consumer loss to producer gain (rent) generated by the tariff, rises with the tariff under very general conditions. This appears as an exception to Becker's view that less distortionary measures tend to be adopted over their more distortionary counterparts. We then provide a micro foundation for our probability definition using the imperfectly discriminating lobbying framework.